Post-Synthetic Enzymatic and Chemical Modifications for Novel Sustainable Polyesters - El-malek, Fady Abd; Steinbüchel, Alexander (Frontiers in Bioengineering and Biotechnology, 2022)
Because of their biodegradability, compostability, compatibility and flexible structures, biodegradable polymers such as polyhydroxyalkanoates (PHA) are an important class of biopolymers with various industrial and biological uses. PHAs are thermoplastic polyesters with a limited processability due to their low heat resistance. Furthermore, due to their high crystallinity, some PHAs are stiff and brittle. These features result sometimes in very poor mechanical characteristics with low extension at break values which limit the application range of some natural PHAs. Several in vivo approaches for PHA copolymer modifications range from polymer production to enhance PHA-based material performance after synthesis. The methods for enzymatic and chemical polymer modifications are aiming at modifying the structures of the polyesters and thereby their characteristics while retaining the biodegradability. This survey illustrates the efficient use of enzymes and chemicals in post-synthetic PHA modifications, offering insights on these green techniques for modifying and improving polymer performance. Important studies in this sector will be reviewed, as well as chances and obstacles for their stability and hyper-production.